Analisis Pengelolaan Retribusi Terhadap Kebutuhan Parkir Kendaraan Bermotor di Pelabuhan Goto sarimalaha. - Usman, Fitri Sarilina; Hi.Muhammad, Amiruddin; Altarans, Indra (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study analyzes the management of motor vehicle parking fees at Goto Sarimalaha Port and its alignment with actual parking needs. Current management is manual, potentially leading to revenue leakage and a lack of public awareness. Therefore, a transparent, accountable, and technology-based system is needed. This research uses quantitative methods, focusing on two- and four-wheeled vehicles, and is expected to provide theoretical benefits for the development of transportation management science and practical benefits for port managers and local governments in improving the efficiency and quality of parking services. Based on the research results at Goto Sarimalaha Port, the motor vehicle parking fee management system is still suboptimal, largely manual, potentially leading to revenue leakage, and a lack of public awareness of payment procedures for visitors. Validity analysis shows that most questions related to fee management have a significant correlation with meeting parking needs, particularly items P3, P4, and P8, which are significant at the 0.01 level. This supports the hypothesis that fee management—including tariff policies, payment systems, and fund allocation—directly contributes to improving parking facilities and meeting port user needs.